Numerical Analysis On the Impact of COVID-19 On The Insurance Industry in Malaysia - Khar Yin, Foo; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2023)
The Coronavirus illness, knowns as COVID-19 has reached pandemic proportions over the world. The virus spread rapidly and the first case of COVID-19 was detected in Malaysia on 25th January 2020. There were many impacts that affected the market of the insurance industry in Malaysia during the COVID-19 pandemic. Hence, the aim of this research is to develop the total income of the insurance industry in Malaysia from 2019 to 2021. Then, we calculate the growth rate of the total income and we get the annual growth rate of 3.75%. After that, we use the exponential growth function and the annual growth rate of the total income of the insurance industry to forecast the total income in the future three years which are 2022, 2023 and 2024. The forecasting graph shows that the total income of the insurance industry in Malaysia has been increasing exponentially over the years. Next, the number of confirmed cases and the number of deaths of COVID-19 diseases are analyzed and a graph was created. We found that the peak of the line graph of the number of confirmed cases falls in August 2021 and the peak of the line graph of the number of deaths falls in September 2021. Not only that, we used the number of deaths to calculate the mortality rate in the population size of 100,000 to create the analysis graph and we found that the mortality rate in 2021 is the highest, which is 0.30999. On the other hand, we also created graph of the case-fatality rate which is calculated by using the number of confirmed cases and the number of deaths. Then, the highest case-fatality rate falls in September 2021 which is 1.9230%. Furthermore, we investigate the relationship between the mortality rate and the total income of the insurance industry by analyzing the data to create the graph. From the result we conclude that the total income of the life insurance industry increases as the mortality rate of COVID-19 diseases increases. We make the hypothesis that the mortality rate increases and most of the insured are willing to buy life insurance to minimize their risk during the COVID-19 pandemic.